The purpose and effectiveness of sales compensation plans - Buehler, Jacob (Kansas State University, 2021)
Sales compensation makes up a large portion of a company’s annual cost. It is, therefore, important for the sales compensation plan to align with the company’s (principal) objectives and motivate the salespeople (agent) to achieve the company goals. An additional goal of the sales compensation plan is to drive sales employee retention, as turnover rates in the sales profession are high as are the replacement costs. The problem addressed by this research into sales compensation plans is twofold. First, to explore the types of sales compensation plans exist and what are their potential effects on employee motivation and retention, and implication on performance for the company. Second, to assess how the alternative compensation systems affect salespeople’s incomes and their motivation to sell. From the foregoing, the research question becomes: To what extent do changes in compensation plans affect employee’s decisions to explore alternative employment? The answer to this question is of benefit to both the employer and the employee. If changes lead to drastic reductions in compensation, even if expected effort declines, it might motivate turnover. The thesis provides a review of the extant literature on sales compensation plans across various industries and how they correlate to employee performance. It also analyzes alternative compensation methods, and explores the effect of compensation downgrading. The analysis uses the case study approach and explores multiple scenarios of Original Auto Parts’ salespeople compensation system. It specifically explores the effect of compensation downgrading on salespeople morale and effort. The study compares Original Auto Parts’ salespeople effort and compensation under the old sales plan and the new plan. The results showed that compensation downgrading was more acute when a salesperson has a larger volume territory than a small sales volume territory. They showed that the two compensations systems had different objectives by what they reward. While the old system rewarded growth, the new system focuses on profitability. While the two objectives can be structured to be congruent, it requires more attention by managers and their management and compensation of their salespeople. The study provided some solutions to addressing these challenges identified with the case study. Original Auto Parts may enhance the base salary of its salespeople to a level that allows them to pursue a profitability pathway that does not adversely affect their original compensation. The company may also use alternative compensation mechanisms, such as bonuses and merchandise, to boost salespeople appreciation of the parity of their compensation under the old and new systems for the same level of effort. If Original Auto Parts fails to match the compensation levels in the two systems, they risk increasing the risk of salespeople turnover increasing. It is important, however, to note that while compensation is a large motivator for salespeople’s decision to stay with a company or seek alternative employment, there are other factors to consider, the importance of which will vary by employee. The salesperson’s values and how they align with the company’s value, or how well they like and work with their team and manager, are intangible factors which also affect a salesperson’s motivation to stay or leave in addition to compensation.
Keywords: Compensation plan; Sales; Agricultural economics; Attrition; Employee retention